JGS Editors’ Choice (Journal of Geographical Systems, 2021)
Background The 4Ms (what matters, medication, mentation, and mobility) is a widely adopted age-friendly care framework. However, there is no evidence on inpatient 4Ms adherence thresholds associated with improved outcomes. Methods In a retrospective cross-sectional analysis, we measured encounter-level adherence to the 4Ms for inpatients 65+ at the University of California San Francisco between January 1, 2021 and December 31, 2024. Outcomes included 30-day unplanned readmissions, 30-day emergency department (ED) visits, length of stay (LOS), and community admissions discharged to a facility. Using fixed effects regression models, we estimated the effect on outcomes of adherence to 100% of 4Ms assessments (what matters, medication, mentation, and mobility screening) plus 25%, 50%, and 75% of shifts with full adherence to 4Ms Act Ons (actions, such as de-prescribing high-risk medications, ambulating). We conducted subgroup analyses by age and medical versus surgical admissions. Results Our study sample included 34,923 inpatient encounters for 22,949 unique patients aged 65+ (mean age 75.3; 49.0% female). We observed lower 30-day readmissions at Act On adherence of 50% (4.1% reduction; 95% CI: 1.8-6.4) and 25% (1.9%; 0.3-3.6). We also found lower 30 day ED visits at 50% Act On adherence in the overall group (3.3%; 0.9-5.8), and in those 85+ (5.0%; 0.4-9.7). Act On adherence and LOS demonstrated a dose-response-like relationship, with 1.0 (0.8-1.1), 1.5 (1.3-1.7), and 1.9 (1.6-2.2) day reductions associated with 25%, 50%, and 75% Act On adherence respectively. No associations were observed between Act On adherence and discharge to facility. Conclusions Higher inpatient adherence to 4Ms care is associated with meaningful reductions in post-acute care utilization and LOS. Our analyses offer clinical leaders guidance on deploying limited resources to positively influence outcomes. They suggest that fully adherent assessments and 25%-50% of shifts with fully adherent Act Ons represent target thresholds.